Association Between Hair Diseases and COVID-19 Pandemic-Related Stress: A Cross-Sectional Study Analysis - Mahadi, Ashrafur Rahaman; Rafi, Md. Abdur; Shahriar, Tasnim; Seemanta, Senjuti; Rabbani, Md. Golam; Akter, Munjarin; Majumder, Mahabubul Islam; Hasan, M. Tasdik (Frontiers in Medicine, 2022)
Introduction: Psychological stress from the ongoing coronavirus disease 2019 (COVID-19) pandemic can potentially aggravate the course of several stress-sensitive skin and hair diseases. This study aimed to determine the potential association of COVID-19 stress with hair diseases, such as telogen effluvium (TE), alopecia areata (AA), and seborrheic dermatitis (SD), among medical students in Bangladesh. Methods This online-based cross-sectional study was conducted among 404 medical students of Bangladesh using a self-administered questionnaire, including sociodemographic information, status of hair diseases (i.e., TE, AA, and SD), COVID-19 fear scale, impact of event scale specific for COVID-19 (IES-COVID-19), and COVID-19 student stress questionnaire (CSSQ) scale, to determine pandemic-related stress. The logistic regression model was used to analyze the association. Results Overall prevalence of TE, AA, and SD was 61.1, 24.7, and 57.7%, respectively, with female predominance in case of TE and male predominance in case of AA and SD. More than half of the participants had COVID-19-related fear and traumatic stress symptoms. In the multiple logistic regression model, smoking [adjusted odds ratio (aOR) 2.93, 95% CI 1.29–6.65 for AA and aOR 4.19, 95% CI 1.83–9.56 for TE], COVID-19-related fear (aOR 1.70, 95% CI 1.01–2.89 for AA and aOR 2.620, 95% CI 1.25–5.48 for TE), and COVID-19-related traumatic stress symptoms (aOR 1.84, 95% CI 1.08–3.13 for AA, aOR 2.61, 95% CI 1.19–5.68 for TE, and aOR 1.92, 95% CI 1.14–3.25 for SD) were the risk factors of hair fall disorders. Conclusion Our study showed that a large number of medical students experienced TE, AA, and SD during the pandemic era. COVID-19-related stress and fear potentially have an association with these diseases.